CARNAL PRACTICES: PORN CONSUMPTION AMONG QUEER EAST ASIAN MEN - Jones, Shawn Suyong Yi (AoIR Selected Papers of Internet Research, 2023)
Despite its ability to arouse and titillate or disgust and anger (and sometimes both simultaneously), porn has only recently been examined through an affective lens. Writing in the inaugural issue of Porn Studies, Susanna Paasonen (2014) advocates for porn studies scholars to consider how the application of affect theory can help us better understand the appeal of pornography. Drawing on Paasonen’s concept carnal resonance and Margaret Wetherell’s (2012) affective practice, I propose the concept _carnal practice_ as a way to examine how one engages and makes sense of online pornography through the affectively felt practice of searching for, finding, and getting off to online pornography. This is done through an analysis of 48 semi-structured interviews, conducted between February 2019 and September 2020 and in 5 countries—Taiwan, South Korea, China, Japan and Canada—in which I discuss how queer East Asian men navigate their respective internet space, are drawn to particular content and platforms that satisfy their desires and curiosities, and make sense of the porn they view. In some instances, participants discussed notions of being drawn to authenticity in porn as well as porn that seems real (that is, most similar to their lived experience), attraction to particular sex acts, scenarios and races, and, in other cases, allowing a platform’s algorithm to help facilitate and fine-tune their desires, to name a few. Although this study focuses specifically on the practices of queer East Asian men, the concept of carnal practice is not limited to this group and has wider application.